Pengelolaan Desa Wisata Berbasis Masyarakat di Desa Mas, Ubud - Haniva Rohmatul Jannah; Ida Ayu Suryasih (JURNAL DESTINASI PARIWISATA, 2019)
This research aims to obtain a clear description, complete and in-depth about the management of the tourist village in Mas Village, Ubud as well as to know the community participation in management of tourist village. Research method that used in this research is descriptive qualitative. Data collection is done by observation, interview, literature study and documentation. Data analysis technique that used is descriptive qualitative analysis technique, such as data collection, data reduction, similar data grouping and data interpretation. The results showed that in the management of Mas Tourism Village can be seen: (1) in the planning aspect type of participation is induced participation; (2) in the organizing aspect type of participation is induced participation; (3) in the actuating aspect type of participation is spontaneous participation; (4) in the controlling aspect type of participation is induced participation. Community participation in the management descripted on three indicators, namely (1) decision making that can be seen on organizing, actuating and controlling, (2) implementation of management that can be seen on planning, organizing, actuating and controlling, (3) sharing profit that can be seen on organizing. Key word: management, community participation, tourist village